Islamic Intellectual Stimulation Leadership: Conceptualisation, Scale Development, and Validation - Terang Jaya, Yadi Fakhruzein; Sodikin, Mohamad; Niati, Asih; Fachrunnisa, Olivia (International Journal of Economics, Management and Accounting, 2024)
This study aims at developing a new leadership concept as result of transformational leadership intervention with Isl?mic values, namely Isl?mic intellectual stimulation leadership, and develop a measurement scale. We collected data from 119 respondents among university leaders in Indonesia. Using exploratory tests and confirmatory factor analysis, we tested the validity and reliability of the proposed measurement scales. The findings of this study reveal 23 indicators that reflect Isl?mic Intellectual stimulation leadership in the Indonesian context. This research contributes to development of the human resources literature especially on the concept of workplace leadership. This research is limited only to Indonesian institutions; to apply these indicators in a broader and global context, future researchers need to conduct similar research at several different institutions or contexts around the world. Professionals can use these findings as a basis for designing and developing leadership qualities in the workplace that can broadly stimulate employees to improve organizational performance.